ANALISIS PENGARUH MEDIA PEMBELAJARAN PHET SIMULATION TERHADAP KETERAMPILAN KOGNITIF SISWA KELAS 5 MATERI RANGKAIAN LISTRIK - Anjar Dwi Setyorini; Nia Nur Afni Fitria; Khofifah Billah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Learning media are objects or platforms that can be manipulated, seen, heard, read, or talked about along with the instruments used for these activities. The existence of differences in students in the ability to receive and understand the knowledge of learning media that has images in it can be an auxiliary tool in channeling understanding of the material This study aims to determine the effect of PhET Simulation media and student learning outcomes on electrical circuit material by combining qualitative methods and quantitative methods. The pre-test average value showed 68.63, while the post-test average value increased significantly to 79.87, showing a substantial increase of 11.24 points. A normality test using the Shapiro-Wilk method confirmed that the data was normally distributed, giving further validity to the findings. Further analysis using the paired sample t-test reinforced this conclusion, with a tcount of -9.263 and a significance value (2-tailed) of 0.000, well below the 0.05 threshold. This means that the difference between the pre-test and post-test is not the result of chance, but reflects the real improvement caused by the use of phet simulation in the learning process